Geoheritage Values Assessment in Aring, Gua Musang, Kelantan. Issue 1 (August 2021) - Sulaiman, N; Udin, W S; Shafiee, N S; Ismail, R
Abstract: The study conducted in the Aring area, with the latitude of 4° 51' 00" N to 4° 58' 17" N and longitude of 102° 19' 24" E to 102° 24' 40" E. Three geological formations existed in this area, namely the Aring Formation, Telong Formation and Koh Formation. The lithology of the Aring Formation includes volcanic rocks such as lapilli tuff, andesite, autobreccia. Other than volcanic, the Aring Formation also consists of limestone, sandstone, and shale. Roughly similar to Aring Formation, the Telong Formation in this area is comprised of Mudstone Unit I, which consists of mudstone, carbonaceous shale, sandstone and tuffaceous mudstone. Koh Formation, however, has quite distinguished lithology and only comprised of sedimentary rocks. The lithology includes conglomerate, sandstone, shale, chert and Mudstone Unit II; carbonaceous lime mudstone and mudstone. Six fossil phyla, namely Echinodermata, Brachiopoda, Cnidaria, Antropoda, Porifera, Mollusca and unidentified trace fossils, were observed in the study as strong evidence of the paleoenvironment of the Aring area. In terms of geoheritage, the fossil occurrences in Aring were determined as regionally significant and essential for that area's regional geology. Fossil is not significant and rare or unique occurrences to classify the fossil occurrences as high rank for geoheritage value. The development of fossil sites over this area can be considered only for educational and scientific purposes. Although fossils were found to be diversely distributed in several locations at Aring, Gua Musang, Kelantan, the levels of significance and value of Total Heritage Value were not high enough to acknowledge the fossils in Aring as a geoheritage potential site.